Desentralisasi, Dinasti Politik dan Kemiskinan di Indonesia - Sujarwoto, Sujarwoto (Jurnal Ilmiah Administrasi Publik, 2015)
This paper examines the link between decentralisation, political dynasty and poverty in Indonesia. Data come from Indonesia Social Economic Survey 2013 and official statistics. Multilevel modelling is used to test whether people live in districts with political dynasty are poorer compared to other districts without political dynasty. The results show people live in districts with political dynasty are significantly poorer and it robust with other individual and district characteristics. The results highlight the detrimental effect of political dynasty on poverty in Indonesia and therefore policy makers should aware of the danger of political dynasty which can impede decentralisation in reducing poverty.